KONSERVASI AIR PADA LAHAN DENGAN KEPADATAN BANGUNAN TINGGI DI KOTA MALANG - Galih Damar Pandulu; Diana Ningrum (Universitas Tribhuwana Tunggadewi Malang, 2018)
The purpose of research expects the settlement arrangement with high density of the building that It returns the land function as water absorption for water conservation. The study goal knows the percentage of land with buildings and green open space in Malang and it is given the solutions for water conservation. The research method practices socio-economic analysis that it know population growth and economic activity. Analysis of spatial use pattern of experimentation area that It know physical suitability. Space structure analysis finds out residential pattern and spatial optimization, hydrological analysis, mechanical analysis and analysis of vertical housing structure. The results of research were obtained in Malang city in general there are 7.789 hectares of built land (70.77%) and 3.217 hectares of open land (29.23%). Klojen and Blimbing sub-districts have open space